Systematic Review on Modern Learning Approaches, Critical Thinking Skills and Students Learning Outcomes - Muhammad Hafeez (Universitas Pendidikan Ganesha, 2021)
The popularity of the internet for using modern and digital learning approaches replaced the old and conventional teaching methods. By applying ICT, an ideal learning environment can be created between students and teachers. The main objective of this review article is to review various dynamic approaches to learning and learning approaches to critical thinking skills and student learning outcomes. This type of research is qualitative. The current investigation was led using enlightenment strategies accumulated by library procedures, which were collected considering educational innovations, related issues, and referenced books. The study results indicate that learning approaches such as Game and Computer-Based or Mobile Based learning approaches are more effective and skilled than conventional learning approaches. Collaborative learning approaches such as Case-Based, Project-Based, and Problem Based learning approaches are very constructive for communication, learning outcomes, and analytical thinking skills. So, a practical and newly developed learning approach should be applied to student learning outcomes of high-level critical thinking and communication skills.